Toxicity of water-accommodated fraction chemically enhanced water-accommodated fraction, and dispersant to selected marine organism - Santander, Sheryll S. (2010.)
The Philippines has suffered two major spills, the Decmber 2005 NAPOCOR spill in Semirara Island, Antique and the August 2006 Solar I spill in Guimaras Island. In each of the spill event dispersant was used as a spill treating agent. However, previous studies showed that dispersants can highly lethal to aquatic organisms. This study assessed the toxicity of water-accomodated fraction (WAF), chemically enhanced water-accommodated fraction (CEWAF), and dispersant (DISP) to local marine species of the Philippines, the Tetraselmis sp., Brachionus rotundiformis, and Chanos chanos and 24th for the Brachionus rotundiformis. Results showed that the addition of dispersant to bunker C oil WAF increased the amount of PAH present in the test solution. The determined EC50 and LC50 values of WAF, CEWAF and DISP suggest that bunker C oil WAF has low toxicity to the selected marine organisms while it shows that the test dispersant alone is toxic to all of the test organisms. The similar toxicity results of CEWAF and DISP together with the low toxicity of bunker c oil WAF and high toxicity of the test dispersant suggest that the mortality in CEWAF is primarily caused by the components of the test dispersant.
Thesis (Graduate, Master of Science in Biology) College of Arts and Sciences, Graduate Program Office, university of the Philippines Visayas, Iloilo City, April 2010.
Keywords: Marine Organisms